Analisis Sarana dan Prasarana Pendidikan Jasmani Olahraga dan Kesehatan Studi Sekolah Menengah Pertama Negeri di Kecamatan Sumbawa Tahun 2023 - Sukarman, Sukarman (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
This study aims to determine how much the level of suitability of physical education learning facilities and infrastructure for public junior high schools in Sumbawa District. The type of research used in this research is descriptive quantitative research that is survey in nature, where in a research that observes, records the condition of objects or subjects in the field. The method in this study was a survey method using observation sheets with techniques for calculating sports and health physical education facilities and infrastructure for junior high schools (SMP) in Sumbawa District. The population in this study is Junior High School (SMP) in Sumbawa District. Based on school data, according to the Ministry of Education and Culture, there are 5 schools according to the suitability of physical education facilities and infrastructure in public junior high schools in the Sumbawa sub-district, showing the level of suitability for each school, namely: 1) SMP Negeri 1 Sumbawa Besar at 64%; 2) SMP Negeri 2 Sumbawa Besar 68%; 3) SMP Negeri 3 Sumbawa Besar 56%; 4) SMP Negeri 4 Sumbawa Besar 56%; and 5) SMP Negeri 5 Sumbawa Besar 52%, and the level of inappropriateness of physical education facilities and infrastructure, namely: 1) SMP Negeri 1 Sumbawa Besar 58.33%; 2) SMP Negeri 2 Sumbawa Besar 37.5%; 3) SMP Negeri 3 Sumbawa Besar 54.16%; 4) SMP Negeri 4 Sumbawa Besar 62.5%; and 5) SMP Negeri 5 Sumbawa Besar 33.3%. Meanwhile, for the suitability of health facilities and infrastructure (UKS): 1) SMP Negeri 1 Sumbawa Besar by 60%; 2) SMP Negeri 2 Sumbawa Besar by 80%; 3) SMP Negeri 3 Sumbawa Besar of 93.33%; 4) SMP Negeri 4 Sumbawa Besar by 60%; and 5) SMP Negeri 5 Sumbawa Besar of 33.33%. The level of incompatibility of facilities and infrastructure, namely: 1) SMP Negeri 1 Sumbawa Besar 40%; 2) SMP Negeri 2 Sumbawa Besar 20%; 3) SMP Negeri 3 Sumbawa Besar 6.66%; 4) SMP Negeri 4 Sumbawa Besar 62.5%; and 5) SMP Negeri 5 Sumbawa Besar 66.66%. The conclusion from the results of this study is that the level of suitability of all Physical Health facilities and infrastructure in Public Junior High Schools in Sumbawa District is ideal with a percentage of 59.2% and 40.8% for non-compliance, while for the health department (UKS) it is ideal with a percentage of 65 .33% and 34.66% for the discrepancy.